2017
DOI: 10.1097/dcr.0000000000000793
|View full text |Cite
|
Sign up to set email alerts
|

Loop Ileostomy Closure as an Overnight Procedure: Institutional Comparison With the National Surgical Quality Improvement Project Data Set

Abstract: Next-day discharge with protocoled diet advancement and telephone follow-up is acceptable after loop ileostomy closure. Patients can benefit from decreased length of stay without an increase in readmission or complications. This has the potential to change the practice of postoperative management of loop ileostomy closure, as well as to decrease cost. See Video Abstract at http://links.lww.com/DCR/A310.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Loop ileostomy closure (LIC) as a seemingly simple procedure was repeatedly associated with considerable morbidity, with overall complication rates of up to 45% and reoperation rates of up to 7% [1][2][3]. More recently, several authors advocated LIC as a same-day procedure in selected patients [4,5]. However, only a few patients were eligible for an ambulant hospital management in a recent analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Loop ileostomy closure (LIC) as a seemingly simple procedure was repeatedly associated with considerable morbidity, with overall complication rates of up to 45% and reoperation rates of up to 7% [1][2][3]. More recently, several authors advocated LIC as a same-day procedure in selected patients [4,5]. However, only a few patients were eligible for an ambulant hospital management in a recent analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that the next-day discharge with protocol diet advancement and telephone follow-up is acceptable after loop ileostomy closure. Patients can benefit from decreased length of stay without an increase in readmission or complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the postoperative care, this should not be a reason to exclude day case ileostomy closure of current practice. If patients are well instructed, and factors for dismissing patients after ambulant surgery are fulfilled, studies have shown ambulant therapy can be applied [23,24]. However, the hospital needs to have the resources to quickly and easily re-hospitalize these patients.…”
Section: Discussionmentioning
confidence: 99%